Artificial intelligence research and development proceedings of the 19th International Conference of the Catalan Association for Artificial Intelligence, Barcelona, Catalonia, Spain, October 19-21, 2016 - Nebot, Angela; Binefa, Xavier; Lopez de Mantaras, Ramon (Frontiers in artificial intelligence and applications, 2016)
Providing an overview of the latest developments in the field, this book will be of interest to all those whose work involves research into, and the application of, artificial intelligence.